RELATIONSHIPS LEVEL OF KNOWLEDGE ABOUT THE BLOOD SUGAR LEVELS OF COMPLIANCE PATIENT DIABETES MELLITUS IN CONTROLLING BLOOD SUGAR IN HEALTH CENTERS DEPOK 3, SLEMAN, YOGYAKARTA - Chasanah, Siti Uswatun; Anida, Anida; Susana, Desi (Jurnal Kesehatan Masyarakat, 2016)
Background: Mellitus Diabetes is a chronic degenerative disease of increasing prevalence. Diabetes Mellitus has characteristics such as hyperglycemia that occurs due to abnormal insulin sekreksi. Insulin or both that cause a variety of chronic complications in the eyes of the kidneys, nerves, and blood vessels. Objective: to determine the relationship of the level of knowledge about the blood sugar levels in Diabetes Mellitus patient compliance to blood sugar control in the health center in Depok 3, Sleman, Yogyakarta. Method: Kind of research is observasional analytic with cross sectional approach. The study population was all patients with Diabetes Mellitus in the health center in Depok 3, Sleman, Yogyakarta, totaling 95 people. A sample size 48 people. Data collection was done bygiving kueaioner to all the respondents of the study. Processing data using Chi Square test with a standard error of 5% and ? = 0,05. Result: Based onbiavariate analiysis there is no relationship between the level of knowledge about the blood sugar levels in Diabetes Mellitus patient compliance to blood sugar control in primary Depok 3, Sleman, Yogyakarta is (p = 0,119). Conclusion: There is no relationship between the level of knowledge about the blood sugar levels in Diabetes Mellitus patient compliance to blood sugar control in health center in Depok 3, Sleman. Yogyakarta. Keyword: diabetes mellitus, blood sugar levels, knowledge, obedience.